Implementation Of Loose Parts-Based Manipulative Media In Learning Activities At Pniel Sikumana Kindergarten - Teti N. Natbais; Irony Damianus Saefatu; Yonatan Foeh; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Background: Loose parts-based manipulative media provide meaningful, play-based learning experiences that support children’s cognitive, motor, creative, and socio-emotional development in early childhood education. However, differences in children’s participation and independence indicate that the implementation of these media has not yet produced optimal learning outcomes for all children. Objective: This study aimed to analyze the implementation of loose parts-based manipulative media in learning activities by examining teachers’ readiness, classroom implementation, and children’s engagement at Pniel Sikumana Kindergarten. Method: This study employed a descriptive qualitative approach. Data were collected through classroom observations, in-depth interviews, and documentation. The participants consisted of one classroom teacher and children aged 4–5 years. Data were analyzed using the Miles and Huberman interactive model through data reduction, data display, verification, and conclusion drawing. The credibility of the findings was ensured through source and technique triangulation. Results: The findings revealed that teachers were well prepared in planning and implementing learning activities using loose parts-based manipulative media. The media increased children’s participation, enthusiasm, exploration, and interaction during classroom activities. Nevertheless, children’s independence varied considerably, and most children still required continuous teacher guidance and repeated demonstrations to complete learning tasks successfully. Teacher scaffolding played a crucial role in maintaining children’s engagement and supporting their gradual development of independent learning behaviors. Novelty: This study highlights that the effectiveness of loose parts-based manipulative media is closely linked to the quality of teacher scaffolding and the gradual development of children’s independence. Conclusion: Loose parts-based manipulative media effectively promote active and meaningful learning experiences. However, their successful implementation depends on systematic teacher guidance, appropriate classroom strategies, and continuous stimulation that gradually fosters children’s independence.